The conservative treatment of low back pain: a study of McKenzie physiotherapy and slow release ketoprofen - Roberts, Andrew (1991)
Acute low back pain: A randomised, controlled, prospective trial of ketoprofen and McKenzie physiotherapy within three weeks of onset.